2017
DOI: 10.1177/0300060517722243
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after arthroscopic single-bundle reconstruction of the posterior cruciate ligament: A 7-year follow-up study

Abstract: ObjectiveArthroscopy is the most popular technique in posterior cruciate ligament (PCL) reconstruction surgery. However, no consensus on long-term outcomes after arthroscopic PCL reconstruction has been reached. This study was performed to evaluate the long-term outcomes after arthroscopic autologous hamstring or allogeneic tendon single-bundle reconstruction of the PCL.MethodsFifty-eight patients who underwent arthroscopic PCL reconstruction in Anhui, China from 2007 to 2009 were included. The follow-up perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…Arthroscopic techniques have been rapidly developed in recent years with respect to minimal trauma and complete removal of synovial tissue from the joint cavity. 8,14,15 In the present case, we observed obvious hyperplasia of the synovial tissue in the ankle joint as well as pannus formation under arthroscopy. However, although arthroscopy can completely debride the synovial tissue and reduce inflammation, it has a learning curve and requires a high level of technical skill to ensure its efficacy.…”
Section: Discussionsupporting
confidence: 61%
“…Arthroscopic techniques have been rapidly developed in recent years with respect to minimal trauma and complete removal of synovial tissue from the joint cavity. 8,14,15 In the present case, we observed obvious hyperplasia of the synovial tissue in the ankle joint as well as pannus formation under arthroscopy. However, although arthroscopy can completely debride the synovial tissue and reduce inflammation, it has a learning curve and requires a high level of technical skill to ensure its efficacy.…”
Section: Discussionsupporting
confidence: 61%
“…Relevant studies have also compared clinical scores. The aforementioned study published by Wang et al [14] in 2017 indicated that the average Lysholm score and Tegner activity score in an autogenous semitendinosus group were 86.2 and 7.68, respectively, whereas those in a hypothermia allogeneic tendon group were 85.0 and 7.74, respectively. A meta-analysis conducted by Tian et al [18] in 2017 demonstrated that the average Lysholm score and Tegner activity score in an autograft group were 82-87.8 and 4.7-7.7, respectively, whereas those in an allograft group were 84-92.3 and 4.7-7.1, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…We reviewed the available research on graft selection and the findings are as follows. Wang et al [14] published a seven-year follow-up study of PCL reconstruction in 2017 and found that the average SSDs were 4.06 mm and 4.20 mm in the autograft group and allograft group, respectively. A retrospective study conducted by Chahla et al [15] in 2017 indicated that the employment of the double-bundle technique for autograft and allograft resulted in an average posterior tibial translation of 2.4 and 4.9 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The average posterior translation SSDs using a hamstring autograft were 4 mm, according to Wang et al [20], while a retrospective study by Chahla et al [21] found that the use of the double-bundle technique for autograft and allograft resulted in posterior tibial translation SSDs of 2.4 and 4.9 mm on average. Both studies used seven-year follow-up data.…”
Section: Discussionmentioning
confidence: 99%